Effect of Pinus halepensis Mill. Reforestation on the Above-Ground Biomass and Internode Elongation and Leaf Size of Native Species in Morroco - Benarchid, Khalid; Khatori, Mohammed; Hilali, Said (European Scientific Journal, ESJ, 2024)
This study aims to determine the effect of the reforestation of Pinus halepensis Mill. on the above-ground biomass and morphological characteristics of native species (internode elongation and leaf size) in the Beni Sohane forest. Plant biomass of the herbaceous layer was harvested on randomly selected 2 m2 quadrats in reforested plots of ± 12, ± 25, and ± 45-year-old, and native forest controls. The internode length and leaf size (length and width) were measured on plants randomly selected belonging to four native species Quercus ilex L., Pistacia lentiscus L., Phillyrea angustifolia L., and Cistus creticus L.. The results showed that P. halepensis reforestation had no significant effect on the above-ground biomass and the leaves and internodes dimensions in the young plantations ± 12-year-old. However, as the pine trees mature, the average dry matter weight decreases, especially in stands 45 years old, where this weight was significantly lower than that of natural forests. This fact has led to herders abandoning important pastures previously used by their cattle. In addition, the fast growth of P. halepensis trees formed a canopy above all indigenous species resulting in changes in the dimensions of internodes and leaves. For the two oldest plantations, the internode length, leaf width, and length of the 4 species have been significantly increased. However, the leaf length-to-width ratio decreased significantly, with leaves in reforested plots being larger rather than longer compared to control samples in native forests. Planting P. halepensis can negatively impact the long-term growth of native plants, so we recommend periodically removing some of the pines (thinning) to restore the balance of these ecosystems. Thus, species selection for reforestation should consider maximizing rather than destroying ecological and socioeconomic services.